Immunization against covid-19 and mortality in hospitalized patients: a retrospective cohort - Alexandre Medeiros de Figueiredo; Adriano Massuda; Michelle Fernandez; Agostinho Hermes de Medeiros Neto; Marcus Carvalho (Universidade de São Paulo, 2024)
ABSTRACT OBJECTIVE To evaluate the effectiveness of vaccines developed against covid-19 in reducing mortality in people hospitalized with severe acute respiratory syndrome (SARS) caused by SARS-CoV-2. METHODS This is a retrospective cohort that evaluated risk factors and the effectiveness of the two-dose vaccination schedule in reducing the mortality of people hospitalized for covid-19 in the state of Paraíba from February to November 2021. The explanatory variables were vaccination status, presence of comorbidities, socioeconomic and demographic characteristics. Descriptive analyses and bivariate and multivariable logistic regression were performed. RESULTS Most hospitalizations and deaths occurred until May 2021. The percentage of patients with a complete vaccination schedule was similar across patients admitted to public and private hospitals and higher in residents of less developed municipalities. Multivariable analysis demonstrated that women (OR = 0.896; 95%CI 0.830-0.967) and people admitted to private hospitals (OR = 0.756; 95%CI 0.679-0.842) were less likely to die. Presence of any comorbidity (OR = 1.627; 95%CI 1.500-1.765) and age ≥ 80 years (OR = 7.426; 95%CI 6.309-8.741) were risk factors for death. Patients with complete vaccination schedule at the time of admission were 41.7% less likely to die (OR = 0.583; 95% CI 0.501-0.679) from covid-19 in the adjusted analysis, as compared to unvaccinated patients. CONCLUSIONS The study reveals that immunization was effective in reducing the likelihood of death from covid-19. The results suggest that greater vaccination coverage in the first half of 2021 would prevent thousands of deaths in the country.